LEGAL VOIDS AND MARKET VOIDS: HOW OUTDATED ADVERTISING LAWS THREATEN MEDIA SUSTAINABILITY IN ARMENIA - Tavadyan, Arsen; Mkhitaryan, Mari (State and Law, 2026)
This study examines the critical challenge of online advertising regulation in Armenia, a post-Soviet country with a transitional democracy. The object of the study is the RA Law “On Advertising”, a legal framework developed in the pre-digital era of television and print, which fails to meet the demands of the modern media environment. The purpose of the research is to analyze the gaps in this legislation and propose practical solutions. The scientific novelty lies in its empirical contribution as a comprehensive study to analyze the direct impact of vague legal concepts and restrictive advertising policies on the financial stability of local media in Armenia. The results show that recent regulations, in particular the near-total ban on gambling advertising, have led to a significant loss of revenue for media organizations, while failing to reduce the overall size of the gambling market. The practical significance of the work is that its findings and recommendations can serve as a roadmap for policymakers to reform the RA Law "On Advertising" and develop effective oversight mechanisms that balance public interest with the need for a free and financially viable press.
Keywords: online advertising; legal regulation; media sustainability; legislative gaps; gambling advertising; post-Soviet media; Armenia; media economics